2007
DOI: 10.1002/jbm.a.30969
|View full text |Cite
|
Sign up to set email alerts
|

Laser microfabrication of hydroxyapatite‐osteoblast‐like cell composites

Abstract: We have developed a novel approach for layer-by-layer growth of tissue-engineered materials using a direct writing process known as matrix assisted pulsed laser evaporation direct write (MAPLE DW). Unlike conventional cell-seeding methods, this technique provides the possibility for cell-material integration prior to artificial tissue fabrication. This process also provides greater flexibility in selection and processing of scaffold materials. In addition, MAPLE DW offers rapid computer-controlled deposition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 47 publications
(35 reference statements)
0
35
0
1
Order By: Relevance
“…1 Previously, pulsed laser printing techniques have shown great promise for printing numerous types of mammalian cells. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pulsed laser cell depositions have shown high cell viability, 4,5,8,[11][12][13][14][15][16] little to no DNA damage, 6,16 unaltered apoptosis rates, 8,16 little to no increase in heat shock protein expression, 11,15 and normal cell proliferation. 8,11,16 Current laser-based direct-write techniques have proven their efficacy and potential; however, many rely on commercially available basement membrane matrix, MatrigelÔ (BD Biosciences, Bedford, MA).…”
Section: Introductionmentioning
confidence: 99%
“…1 Previously, pulsed laser printing techniques have shown great promise for printing numerous types of mammalian cells. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Pulsed laser cell depositions have shown high cell viability, 4,5,8,[11][12][13][14][15][16] little to no DNA damage, 6,16 unaltered apoptosis rates, 8,16 little to no increase in heat shock protein expression, 11,15 and normal cell proliferation. 8,11,16 Current laser-based direct-write techniques have proven their efficacy and potential; however, many rely on commercially available basement membrane matrix, MatrigelÔ (BD Biosciences, Bedford, MA).…”
Section: Introductionmentioning
confidence: 99%
“…They subsequently showed that sequential deposition of nHAp alongside human osteoprogenitors in alginate onto Matrigel™ substrates could be used to pattern these components in 2D and 3D with retention of cellular function for application in bone TE . Deposition of nHAp alongside osteoblast-like cells has also been demonstrated by a MAPLE-DW approach (Doraiswamy et al 2007). …”
Section: Current Progress Chrisey Et Al First Demonstrated the Maplementioning
confidence: 99%
“…This result suggested that MG 63-hydroxyapatite composites could be extended to develop integrated cell-scaffold structures for medical and dental applications. 76 To treat bone metabolic disorders, MAPLE fabrication technology was used to create alendronate-hydroxyapatite (HA-AL) nanocrystal thin films on titanium (Ti) substrates to test the effects on osteoblasts and osteoclasts. In the presence of thin films, the osteoblast-like MG63 cells displayed normal morphology, increased proliferation, and differentiation compared to control.…”
Section: Biomaterials Deposition Using Matrix Assisted Pulsed Lasementioning
confidence: 99%
“…Doraiswamy et al used triazine polymer as an intermediate absorbing layer and transferred viable B35 neuroblasts using MAPLE. 76,78 After transferring viable B35 neuroblasts onto receiving substrates, the cell viability and proliferation were examined to show that the MAPLE deposition technique, coupled with an intermediate absorbing layer, was acceptable for creating patterns of viable cells at low fluency. Using MAPLE technology, researchers deposited PLGA/PU polymer to fabricate the substrate topography to study cell viability and preferential orientation of oral keratinocyte stem cells.…”
Section: Biomaterials Deposition Using Matrix Assisted Pulsed Lasementioning
confidence: 99%